Expanding knowledge on emotional dynamics and viewer engagement: The role of travel influencers on youtube - Jinyoung Jinnie Yoo; Heejin Kim; Sungchul Choi (Journal of Innovation & Knowledge (JIK), 2024)
This study investigates how the discrete emotions expressed by travel influencers on YouTube influence viewer engagement, distinguishing between macro- and micro- influencers. Using text mining and machine learning techniques, 6,061 travel-related videos were analyzed. The results indicate that high-arousal negative emotions such as anger and disgust enhance engagement for macro-influencers but reduce engagement for micro- influencers. Conversely, low-arousal negative emotions, such as fear and sadness, increase engagement levels for micro-influencers, while decreasing them for macro-influencers. Positive emotions enhance engagement, particularly among micro-influencers. These insights can inform emotional strategies in influencer marketing.
Keywords: M30; 650; Emotions; Influencer marketing; Travel; Youtube; Engagement; Text-mining